THE IMPORTANCE OF FINANCIAL RATIOS IN FINANCIAL ANALYSIS OF BUSINESS ENTITIES (Globalization and Business, 2018)
The paper refers to the specificities of usage of analytical  financial tools in real sector of economy in Georgia, also inevitability of taking into consideration of analytical nuances by financial practitioners.In the article the importance of financial ratios utilization is highlighted. The following peculiarities are also considered and analysed:1. Selection of financial ratios; 2. Period of calculation of ratios; 3. Normativity of financial ratios; 4. Combined usage of ratios; 6. Sector specific financial ratios. It should be noted that analytical financial tools such as financial ratios are only used in Georgian business entities in following cases: economic entity represents corporate business; company has a good arranged management system; it is a branch of foreign firm; company is in tight coordination with financial institute, etc.The paper refers to the most important issues of the country’s corporate finance as follows: classification of enterprises for reporting goals, managerial reporting aspects, functions of regulator state organ, financial statements quality, companies’ accountability from auditing point of view, prerequisites the usage of international financial reporting standards (IFRS), inevitability of formation of financial benchmark system. It should be noted that the average sector benchmarks are not calculated in Georgian transitional economy that makes impossible for companies to compare their financial performance measures to the average sector/subsector financials. The consolidation and concentration process of financial and managerial reporting stimulates the utilization of analytical financial tools which increases the quality and access  of relevant and reliable financial information flows.